Analisis Pelaksanaan Mutasi Jabatan di Pemerintah Kabupaten Luwu Utara - Muhammad Wahyu; Andi Gau Kadir; Andi Lukman Irwan (Departemen Ilmu Pemerintahan Fisip Unhas, 2012)
Abstract: This study aims to obtain a description or explanation of the implementation of positions of mutations in Luwu Utara District Government is already in line with the competence of civil servants in their respective fields and what are the implications of political, governmental, and administrative positions in the implementation of mutations in Luwu Utara District Government. The results of this study are expected to be input or evaluation for local governance institutions in the implementation of the District Forestry office mutations in Luwu Utara. In terms of academic, results from this study are expected to be useful for the development of the repertoire of the science of government, especially the study of mutation positions. The results showed that the mutation positions in Luwu Utara District Government held in order to refresh the organization in order to avoid saturation for civil servants as well as for career advancement of civil servantsKeywords : Shakeup Position, civil servant, Human Recources ManagementAbstrak: Penelitian ini bertujuan untuk memperoleh gambaran atau penjelasan tentang pelaksanaan mutasi jabatan di Pemerintah Kabupaten Luwu Utara apakah sudah sesuai dengan kompetensi PNS di bidangnya masing-masing dan bagaimana implikasi politik, pemerintahan, dan administratif dalam pelaksanaan mutasi jabatan di Pemerintah Kabupaten Luwu Utara. Hasil dari penelitian ini diharapkan dapat menjadi bahan masukan atau evaluasi bagi lembaga pemerintahan daerah Kabupaten Luwu Utara dalam pelaksanaan mutasi jabatan di Kabupaten Luwu Utara. Dari segi akademik, hasil dari penelitian ini diharapkan dapat bermanfaat bagi perkembangan khasanah ilmu pemerintahan terutama kajian tentang mutasi jabatan. Dari hasil penelitian menunjukkan bahwa mutasi jabatan di pemerintah Kabupaten Luwu Utara diselenggarakan dalam rangka penyegaran organisasi agar tidak terjadi kejenuhan bagi PNS serta untuk peningkatan karir PNS.Kata kunci : Mutasi jabatan, PNS, Manajemen SUmber Daya Manusia